Misconceptions between Social Studies and Social Sciences among Pre-Service Elementary Teachers - Miftakhuddin, Miftakhuddin; Mustadi, Ali; Zulfiati, Heri Maria (International Journal of Education, 2019)
This quantitative study was conducted to identify the misconception between social studies and social sciences among pre-service elementary teachers. Data were collected from the subjects (n=122) drawn by cluster sampling in Yogyakarta. Aiken's validity and Cronbach Alpha were then employed to examine the instrument's quality. Collected data were analyzed using descriptive techniques to examine the level of misconception. The popular misconceptions between social studies and social sciences were identified by the criteria developed by Abraham, Grzybowski, Renner, Marek (1992). The results of the study show that there was a greater understanding of social studies and social sciences for the specific fields of geography, anthropology, and politics. Therefore, the main emphasis should be placed on these fields. The fields that were misconceived included economics, geography, and history. The implications of this research will eventually become the basis and guideline for social studies lecturers to give emphases on the fields of study belonging to social studies, distinguishing them from those of social sciences. In addition, each social science discipline adopted into social studies must receive special attention, given the greater level of misconception among the pre-service teachers in these fields.